Biases in FX-Forecasts: Evidence from Panel Data - David B. Audretsch; Georg Stadtmann (Deutsche Bank Research, 2005)
In this paper, we use the Wall Street Journal poll of FX forecasts to analyze how the group of forecasters form their expectations. One focus is whether forecasters build rational expectations. Furthermore, we analyze whether the group of forecasters can be regarded as homogeneous or heterogeneous. The results from our regressions strongly suggest that some forecasters combine different models of exchange rate forecasting, while others rely solely on one model. We also find evidence that some forecasters underly a bias, while others do not. Overall, our regression results indicate a high degree of heterogeneity. In conclusion, we show that the expectation formation process is not the same among all economists polled. Our findings carry importance for macroeconomic modelling: The assumption of rational agents forming homogeneous expectations is not supported by our results.
Keywords: C33; D84; F31; 330; Foreign exchange market; forecast bias; random walk; Wechselkurs; Prognoseverfahren; Anlageberatung; Erwartungstheorie; Bias; Devisenmarkt; Random Walk; Schätzung; Vereinigte Staaten; Finanzanalyst